Sub-paddock scale spatial variability between the pasture and cropping phases of mixed farming systems in Australia - McEntee, P.; Belford, Robert; Mandel, Roger; Harper, J.; Trotter, M. (Wageningen Academic Publishers, 2013)
Precision farming techniques are now widely applied within Australian cropping systems. However, the use of spatial monitoring technologies to investigate livestock and pasture interactions in mixed farming systems remains largely unexplored. This paper builds on previously reported work that is using remote sensing technologies to investigate livestock and pasture interactions in the pasture phase and to follow the after-effects of different management strategies into a subsequent cropping phase. Experimental data has been gathered from two dryland cropping sites, one in Western Australia (annual pasture system) and one in north-eastern Victoria (perennial pasture system). Smoothed time series of weekly NDVI composites were constructed by means of the adaptive Savitzky-Golay filter. Eight complete phenological cycles (2004-2011) were processed and eleven phenology metrics were calculated for each cycle. The analysis reinforces previous results that indicated spatial variation in biomass between pasture and cropping phases is consistent and correlated over time. In the annual pasture system, two metrics showed strong correlation between cropping and pasture phases – end of season biomass and peak NDVI. In the perennial pasture system, strong correlations were observed for seven metrics – end of season biomass, time of season onset, end of season, season duration, peak NDVI, season amplitude and rate of NDVI decrease.